Visual prognosis of massive submacular hemorrhage in polypoidal choroidal vasculopathy with or without combination treatment. Issue 3 (March 2016) - Lin, Tai‐Chi; Hwang, De‐Kuang; Lee, Fenq‐Lih; Chen, Shih‐Jen
Abstract : Background : Submacular hemorrhage associated with polypoidal choroidal vasculopathy (PCV) may cause severe visual loss. The purpose of this study is to report the visual prognosis of massive submacular hemorrhage in patients with PCV. Methods : Twenty patients with PCV and submacular hemorrhage who received either subretinal tissue plasminogen activator (TPA) with vitrectomy or intravitreal injection of TPA and gas to achieve pneumatic displacement of the hemorrhage were enrolled. Additionally, combination treatment with either photodynamic therapy (PDT) or intravitreal injection of vascular endothelial growth factor inhibitors (anti‐VEGF) was performed to treat the underlying PCV. Results : Five patients received subretinal TPA with vitrectomy and 15 patients received intravitreal injection of TPA and gas to remove or displace the submacular hemorrhage. Combination treatment with PDT and intravitreal anti‐VEGF was performed in three patients and intravitreal anti‐VEGF injection alone in 13 patients. The mean logarithm of the minimal angle of resolution converted from the best corrected visual acuity (BCVA) were improved at 3 months, 6 months, and 12 months. Better initial BCVA, smaller size of submacular hemorrhage and younger age were statistically significant predictors for BCVA. Combination treatment with PDT showed significant efficacy in the improvement of BCVA. Conclusion : Combination treatment of submacular hemorrhage secondary to PCV may yield visual and anatomic improvements. Initial BCVA, the initial size of submacular hemorrhage and age were significant predictors for visual prognosis.